Infection-Related Activation of the cg12 Promoter Is Conserved between Actinorhizal and Legume-Rhizobia Root Nodule Symbiosis - Svistoonoff, Sergio (2004)
Two nitrogen-fixing root nodule symbioses between soil bacteria and higher plants have been described: the symbiosis between legume and rhizobia and actinorhizal symbioses between plants belonging to eight angiosperm families and the actinomycete Frankia. We have recently shown that the subtilisin-like Ser protease gene cg12 (isolated from the actinorhizal plant Casuarina glauca) is specifically expressed during plant cell infection by Frankia. Here we report on the study of C. glauca cg12 promoter activity in the transgenic legume Medicago truncatula. We found that cg12 promoter activation is associated with plant cell infection by Sinorhizobium meliloti. Furthermore, applications of purified Nod factors and mycorrhizal inoculation failed to trigger expression of the cg12-reporter gene construct. This indicates that at least part of the transcriptional environment in plant cells infected by endosymbiotic nitrogen-fixing bacteria is conserved between legume and actinorhizal plants. These results are discussed in view of recent data concerning molecular phylogeny that suggest a common evolutionary origin of all plants entering nitrogen-fixing root nodule symbioses.